THE ROLE OF ESG AND DIGITAL TRANSFORMATION IN MARKET REACTIONS EVIDENCE FROM EARNINGS MANAGEMENT AND ERC - Sri Retnoningsih; Sekar Dian Pramesti Suryo; Wulandari Syarifatul Ulya; Retdating Retnowati (Universitas Dian Nuswantoro, 2026)
ABSTRACT This study aims to analyze the effect of Earnings Management, Environmental, Social, and Governance (ESG), and Digital Transformation on the Earnings Response Coefficient (ERC) in telecommunications companies listed on the Indonesia Stock Exchange for the period 2020–2024. Using a quantitative method with Partial Least Squares (PLS) analysis, this study consists of 51 companies selected purposively. The results show that Earnings Management has a significant negative effect on ERC, while ESG and Digital Transformation have a significant positive effect. The R² value of 0.62 indicates that the model has a strong power over ERC variation. These findings confirm that sustainability practices and digitalization strengthen the credibility of financial reports and investor confidence, whereas earnings management reduces the quality of earnings information. The implications for accounting education are the need to strengthen he reporting ethics curriculum, integrate ESG, sustainability accounting, and develop digital competencies hat support transparency. Thus, accounting education must produce accountants who are not only technically proficient, but also committed to ethics, sustainability, and responsible governance